Analisis transaksi e-commerce dan modal terhadap peningkatan pendapatan usaha mikro kecil dan menengah dalam perspektif Islam - Rimi Gusliana Mais; Saiful Muchlis; Munir Munir; Aski Khoirunnisa (LPMP Imperium, 2023)
This study focuses on culinary micro, small and medium enterprises (MSMEs) in Kelapa Gading District. According to research findings, most informants adhere to Islamic law-based ethical standards to conduct business, such as maintaining product quality, using high-quality raw materials, providing excellent customer service, being friendly to customers, and making reasonable arrangements for prices. Most informants know and are proficient in using the bai'as-salam contract in legal e-commerce transactions. However, some do not understand because of their ignorance. E-commerce is a digital banner that everyone can see. It makes it easier to get customers and makes running a business more profitable. Business actors prefer to use personal capital because it has several advantages, such as reducing operational costs, minimizing losses, thinking about hiring employees, and managing successful marketing Public interest statementThe results of this study can add new insights for MSME owners in running their businesses while adhering to Islamic values. Article HistoryReceived 31 Mar 2022 | Revised 10 Dec 2022 | Accepted 15 Dec 2022 | Online First 03 Jan 2023